Manejo agronómico del cultivo de Tamarindo (Tamarindus indica) - Anchundia Salazar, Jefferson Rafael (2021)
This document details the agronomic management of the Tamarind (Tamarindus indica) crop. Its tree is considered an economic impact in other countries for its medicinal benefits. The conclusions determine that this review observed and analyzed the evidence supporting the beneficial effects on health with the consumption of tamarind. Likewise, these effects are due to its content of polyphenolic compounds and other compounds that are attributed to the reduction of chronic degenerative diseases. However, more research is needed to observe the bioavailability of these tamarind compounds and to have more exact scientific evidence of the importance from a nutritional and functional point of view and the research work carried out over the years has generated information that has It has been possible to know its taxonomic identification and agronomic characteristics in other countries, but there is no information from Ecuador. The proposed recommendations are to carry out studies in Tamarindo (Tamarindus indica) in Ecuador and to encourage farmers to produce and commercialize it as an alternative for economic income.